Glycine Potentiates AMPA Receptor Function through Metabotropic Activation of GluN2A-Containing NMDA Receptors - Li, Li-Jun; Hu, Rong; Lujan, Brendan; Chen, Juan; Zhang, Jian-Jian; Nakano, Yasuko; Cui, Tian-Yuan; Liao, Ming-Xia; Chen, Jin-Cao; Man, Heng-Ye; Feng, Hua; Wan, Qi (Frontiers in Molecular Neuroscience, 2016)
NMDA receptors are Ca2+-permeable ion channels. The activation of NMDA receptors requires agonist glutamate and co-agonist glycine. Recent evidence indicates that NMDA receptor also has metabotropic function. Here we report that in cultured mouse hippocampal neurons, glycine increases AMPA receptor-mediated currents independent of the channel activity of NMDA receptors and the activation of glycine receptors. The potentiation of AMPA receptor function by glycine is antagonized by the inhibition of ERK1/2. In the hippocampal neurons and in the HEK293 cells transfected with different combinations of NMDA receptors, glycine preferentially acts on GluN2A-containing NMDA receptors (GluN2ARs), but not GluN2B-containing NMDA receptors (GluN2BRs), to enhance ERK1/2 phosphorylation independent of the channel activity of GluN2ARs. Without requiring the channel activity of GluN2ARs, glycine increases AMPA receptor-mediated currents through GluN2ARs. Thus, these results reveal a metabotropic function of GluN2ARs in mediating glycine-induced potentiation of AMPA receptor function via ERK1/2 activation.